Manajemen Lalu Lintas Di Jalan Akasia Guna Menghindari Kemacetan - I Made Suniastha Amerta; Luh Putu Sudini; Ni Made Widya Pratiwi Widya Pratiwi (Jurnal Abdi Daya, 2021)
Warmadewa University is a large university in Bali which has faculties, study programs, and postgraduate programs with a total of 7 active students. Currently operational Univ. Warmadewa is still centered on Jalan Terompong Number 24, Denpasar and has 3 exits, namely the main Akasia Street, Jalan Akasia XVI, and Jalan Akasia which is Ex IKIP / Paud Erlangga. Development of Univ. Warmadewa, which was founded in 1984, has brought quite rapid changes to the surrounding lands, which were formerly agricultural land, now become densely populated settlements, boarding houses for students and traders, photocopying, laundry, and others which are a significant impact as a result. the Warmadewa University campus. The condition of economic development around Warmadewa University can be seen from the proliferation of stalls and shops where you can sell which has an impact on the crowded parking and traffic around it. At night, this condition is getting denser without being accompanied by improvements in road facilities being the main problem in this PKM. Furthermore, the solution that can be offered is to carry out data collection on traffic facilities on the main Akasia Street and Akasia XVI in the hope that it can foster awareness and participation of the community to care more about the surrounding environment and Warmadewa University as the center of economic awakening can also help the surrounding community.